Identifying Perception, Interests and Challenges of Informatics Students on Online Learning During COVID-19 Outbreaks - Emigawaty Emigawaty (Universitas Bina Darma, 2021)
Since the COVID-19 outbreak is increasingly widespread in Indonesia at the beginning of the year 2020, the government considers taking policies that focus on implementing the learning and teaching process at all levels. This research focuses on identifying the perception, interests, and challenges of online learning for informatics’ students at AMIKOM University Yogyakarta during the global pandemic. This study uses a descriptive quantitative approach using a survey instrument. This research has succeeded in capturing an overview of the ease, obstacles, and challenges of the informatics’ students in joining online learning from the study results. Discussions and contradictions to these results will undoubtedly be different if they are carried out on different student entities and with various subjects. This research contributes to higher education institutions, especially AMIKOM Yogyakarta University, to evaluate the online learning process. Although the case study presented in this research cannot represent other subjects, students' perceptions can be used as essential feedback for educational institutions.